(untitled) (BIRDEM Medical Journal, 2014)
Idiopathic thrombocytopenic purpura (ITP) is an autoimmune disease where low platelet counts predisposeto various bleeding tendencies; intracranial haemorrhageis one of them. It is a rare and devastating complication of ITP, mostly presenting as intracerebral (ICH) or subarachnoid haemorrhage (SAH). Here, we report a 32-year-old splenectomized chronic ITP patient on corticosteroid and azathioprine, in whom spontaneous SAH developed. In this case, conservative management resulted in clinicoradiological improvement and showed eventual favourable out-come. Birdem Med J 2014; 4(2): 105-107